Carotid artery stenting in the context of endovascular treatment of acute ischemic stroke - Lucena, Adson F. de; Castro-Afonso, Luís Henrique de; Monsignore, Lucas M.; Nakiri, Guilherme S.; Fábio, Soraia R. C.; Pontes, Octávio, Neto; Abud, Daniel Giansante (Arquivos de Neuro-Psiquiatria, 2016)
Mechanical thrombectomy as an adjunctive to intravenous thrombolysis is now the standard treatment for acute ischemic stroke (AIS) due to large vessel occlusions. However, the best management of acute carotid tandem occlusions (CTO) remains controversial. Method Twenty patients underwent endovascular treatment of acute CTO. The primary endpoint was the composite rate of complete or partial recanalization without a symptomatic intracranial hemorrhage (sICH). Secondary endpoints were recanalization times, procedure times, and clinical outcomes at three months.Results The primary endpoint was reached in 17 (85%) patients. Recanalization rate was reached in 90% of patients (19/20) and sICH rate was 5% (1/20). At the 3-month follow-up we obtained a mRS ≤ 2 rate of 35% (7/20) and a mortality rate of 20% (4/20).Conclusion Carotid angioplasty stenting and endovascular treatment of AIS due to CTO appears effective with an acceptable rate of sICH.
Keywords: acute ischemic stroke; symptomatic carotid artery stenosis; carotid angioplasty stenting